Tecnologia pós-colheita de modificação atmosférica, controle do etileno e desverdecimento para a banana 'Prata-Anã cultivada em Boa Vista, Roraima - Prill, Marcos André de Souza (Universidade Federal de Roraima, 2022)
The banana culture is one of the highlights at the Roraima State, in the agribusiness sector, representing significance in the fruit market, however, leaves much to be desired on the final quality to the consumer. In this sense, it was conducted 2 experiments, where, at the 1st it was evaluated the postharvest quality of bananas 'Prata-Anã' subjected to cold storage (CS) at a temperature of 12 ± 1°C and relative humidity (RH) of 93 ± 2% in the cold chamber, located at the Food Technology Laboratory (LTA/UFRR). In this experiment, the refrigerated bananas were packed in low density polyethylene (LDPE), with and without the use of vacuum and use of ethylene adsorption inside the package. Analyses were performed at 5 days after harvest until 35 days of cold storage. In the experiment 2, based on the scores of the 1st experiment, it was evaluated the degreening of the fruits by the technology use of phytoregulator and muffling, using plastic blanket (polyethylene wired raffia inside and eyelets brass), performed without atmospheric control (t °C, RH) and at different times of bananas cold storage (on the harvest, and at 10, 20 and 30 days of CS). Analyses were performed sequentially at 1, 2, 3 and 4 days after each degreening period. The physical, chemical and physico-chemical analyses, in both experiments were conducted on the pH of the pulp, loss of fresh weight, peel color, soluble solids (SS), titratable acidity (TA), CO2/etileno concentration inside the package, respiratory pattern (CO2/etileno) total and reducing sugars, enzymatic activity of polygalacturonase (PG) and pectin methyl esterase (PE) and total and soluble pectin content and starch content. At the end of experiment 1 it was concluded that the combination of the polyethylene bags with the ethylene adsorbents sachets resulted in the delaying of the bananas ripening process, when observed the respiration pattern in relation to the delay of the climacteric peak of fruits packed with the ethylene adsorption sachet. Likewise, it was observed the technology effect on the ethylene adsorption sachet inside the package, reflecting the better maintenance of sensorial quality according to the scores observed in the physical, chemical and physico-chemical analysis. In the experiment 2, in the end of 4 days of storage, it was observed that there was not effect that would determine the best method of degreening, but it was found that the longer the period of RA, lower was the maintenance of the period of quality of bananas 'Prata-Anã' after the degreening. Thus, it is possible recommend that the degreening be perfomed with safely until 20 days after harvest and especially if the banana 'Prata-Anã' kept under cold storage at 12° ± 1 °C and 93 ± 2% RH. It is hoped, in this situation, the maintenance of sensorial quality attributes for bananas at least for 3 days during the average marketing at the Roraima State.